2015
DOI: 10.1111/acel.12317
|View full text |Cite
|
Sign up to set email alerts
|

Subacute calorie restriction and rapamycin discordantly alter mouse liver proteome homeostasis and reverse aging effects

Abstract: Calorie restriction (CR) and rapamycin (RP) extend lifespan and improve health across model organisms. Both treatments inhibit mammalian target of rapamycin (mTOR) signaling, a conserved longevity pathway and a key regulator of protein homeostasis, yet their effects on proteome homeostasis are relatively unknown. To comprehensively study the effects of aging, CR, and RP on protein homeostasis, we performed the first simultaneous measurement of mRNA translation, protein turnover, and abundance in livers of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
99
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 40 publications
12
99
3
Order By: Relevance
“…(2015) recently published an elegant study that is highly complementary to the results presented here and provides mechanistic insights into improved proteostasis in two of the three models evaluated here. Using heavy‐leucine labeling, this group found that 10 weeks of 40% CR in 25‐month‐old mice and 10 weeks of 14 ppm Rapa treatment in 3‐month‐old mice reduced hepatic protein RRs by 30% and 13%, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…(2015) recently published an elegant study that is highly complementary to the results presented here and provides mechanistic insights into improved proteostasis in two of the three models evaluated here. Using heavy‐leucine labeling, this group found that 10 weeks of 40% CR in 25‐month‐old mice and 10 weeks of 14 ppm Rapa treatment in 3‐month‐old mice reduced hepatic protein RRs by 30% and 13%, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…These results are consistent with a recent study employing short‐term (10 weeks) 40% CR in older mice (25‐month‐old). Using heavy‐leucine labeling, these authors observed a ~33% reduction in hepatic protein RRs in CR compared to AL mice (Karunadharma et al ., 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the more efficient suppression of age-associated epigenetic changes by CR, the epigenetic effects of CR and rapamycin were not identical and this might further underlie some of the differences between them that have been noted in previous studies, for example in endocrine and metabolic phenotypes and gene expression profiles [55, 62]. Of note, rapamycin in particular appears to induce additional changes unrelated to age-associated changes.…”
Section: Discussionmentioning
confidence: 77%
“…Emerging evidence suggests that caloric restriction augment autophagy activity in many organs including skeletal muscle [36], liver [37], kidney [38], heart [39], and brain [40] in rodents. In this study, we provide further evidence that caloric restriction promotes autophagy function of adipose tissue SVFs (Fig.…”
Section: Discussionmentioning
confidence: 99%